2023
DOI: 10.1111/acfi.13135
|View full text |Cite
|
Sign up to set email alerts
|

Higher‐order moments and asset pricing in the Australian stock market

Abstract: This paper investigates a set of realised higher‐order co‐moment risk–return relationships in the Australian stock market. We test the predictive power of the asset pricing model by implementing the two‐, three‐, four‐moment Capital Asset Pricing Model. Our findings show that investors respond differently to information related to realised higher‐order co‐moments, and that the corresponding gamma (normalised co‐skewness) and kappa (normalised co‐kurtosis) risk factors remain priced in the presence of continuou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 108 publications
(249 reference statements)
1
1
0
Order By: Relevance
“…As confirmed by the results, the three-moment CAPM downside co-skewness is priced, while the conventional counterpart of this coefficient turned out to be insignificant. Similar results were obtained, for example, in the work of Ahadzie and Jeyasreedharan (2023).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…As confirmed by the results, the three-moment CAPM downside co-skewness is priced, while the conventional counterpart of this coefficient turned out to be insignificant. Similar results were obtained, for example, in the work of Ahadzie and Jeyasreedharan (2023).…”
Section: Discussionsupporting
confidence: 89%
“…Based on shares in the British, German and French capital markets, Dong et al (2022a) showed the use of higher moment values to reduce the risk of changes in market dynamics, especially the downside risk. A significant valuation of co-moments was also confirmed on the Australian equity markets (Ahadzie & Jeyasreedharan, 2023).…”
Section: Literature Reviewmentioning
confidence: 58%